Kontribusi Balikan dalam Menunjang Keefektifan Pembelajaran - Punaji Setyosari (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
Feedbacks has three components: feedbacks are given after learners show certain behavior; the feedbacks can be observed by the learners, and feedbacks described the influence of the learners’ behavior. Proponents of behavioristic psychology view feedbacks as reward and punishment which can automatically strengthen or weaken the tendency to give certain response. Proponents of cognitive psychology view feedbacks as information, and learners interpret and use these inputs to change what they already know.